Selective targeting of tumor cells and tumor associated macrophages separately by twin-like core–shell nanoparticles for enhanced tumor-localized chemoimmunotherapy. Issue 29 (15th July 2019) - Wang, Tianqi; Zhang, Jing; Hou, Teng; Yin, Xiaolan; Zhang, Na
Abstract : Twin-like core–shell nanoparticles (TCN) could modify two drugs with similar biodistribution for selective targeting delivery in cancer combination therapy. Abstract : Tumor associated macrophage (TAM)-based immunotherapy has been presented as a promising strategy in cancer therapy. The combination of TAM-based immunotherapy with sorafenib (SF) could be conceivably quite more effective in hepatocellular carcinoma (HCC) treatment. A co-delivery system was superior in improving the co-accumulation of two drugs in tumor tissues for chemoimmunotherapy, while in the case of selective targeting of separated cells such as tumor cells and immune cells, a novel targeted co-delivery strategy was badly required. In this study, twin-like core–shell nanoparticles (TCN) were developed for synchronous biodistribution and separated cell targeting delivery of SF and TAM re-polarization agents IMD-0354 to cancer cells and TAM to enhance tumor-localized chemoimmunotherapy, respectively. First of all, SF loaded cationic lipid-based nanoparticles (SF-CLN) and mannose-modified IMD-0354 loaded cationic lipid-based nanoparticles (M-IMD-CLN) were prepared, respectively. SF on the surface of SF-CLN and mannose on the M-IMD-CLN were regarded as targeting ligands for selective targeting delivery of SF-CLN and M-IMD-CLN to cancer cells and TAM separately. Then, pH-responsive charge reversal polymer O -carboxymethyl-chitosan (CMCS) was coated on the SF-CLN and M-IMD-CLN to obtain twin-like CMCS/SF-CLN and CMCS/M-IMD-CLN, respectively. The results of cellular uptake assay on Hepa1-6 cells and RAW 264.7 cells in vitro, respectively, as well as the results of tumor tissue distribution of SF and IMD-0354 in vivo suggested that CMCS/SF-CLN and CMCS/M-IMD-CLN exhibited similar properties in vitro and synchronous biodistribution in vivo, and were efficient at separated cell targeting delivery. What's more, the results of antitumor efficiency in vivo and phenotype analysis of TAM in tumor tissues proved that CMCS/SF-CLN and CMCS/M-IMD-CLN exhibited superior synergistic antitumor efficacy and M2-type TAM polarization ability compared with SF treatment in Hepa1-6 tumor bearing mice. Consequently, TCN which was the combination of co-administration and nano-drug delivery systems has great potential to be used in tumor-localized chemoimmunotherapy in clinics.